Pure Ideology: the "Ownership Split" of Power Companies in the 1998 Electricity Reforms - Kalderimis, Daniel (Victoria University of Wellington Law Review, 2000)
In April 1998 the New Zealand Government announced a reform package for the electricity industry. This package was designed to create the competition promised since deregulation first began in 1987. The 1998 reforms had two main aspects: first, the split of the Electricity Corporation of New Zealand (ECNZ), New Zealand's dominant state-owned enterprise (SOE) generator, into three competitive units; second, a rule business (the ownership split) that local power companies could not own both a lines business (the local distribution wires) and a generation or retail. The ownership split caused a revolution in the industry. Effectively, small community-owned companies were forced to sell their retail and generation businesses to larger companies or to the State, in the form of the ECNZ "babies". The Government believed that the ownership split would facilitate retail competition and deliver lower domestic power prices. This article asks whether the Government was right – whether the ownership split was necessary, or able, to reduce domestic power prices. It concludes that the ownership split was a staggering mistake. The Government's reasoning was based on inconclusive evidence, inadequate research, and contained major logical flaws. The Government rejected unanimous policy advice warning against the split. Since the split, average domestic power prices have risen by almost four per cent. A major factor is the demise of community-owned supply companies which had offered unique advantages to consumers. The root of this disaster was ideological bias. The Government did not understand the electricity industry but treated it as an abstract economic construct. This article documents the way in which ideology led the Government to wreak havoc on an industry in order to cure problems which did not exist.